Convenient and Environment-Friendly Synthesis of Sulfonyl Chlorides from S-Alkylisothiourea Salts via N-Chlorosuccinimide Chlorosulfonation - Yang, Zhanhui; Xu, Jiaxi (Synthesis, 2013)
A convenient, practical, and environmentally friendly method for the synthesis of sulfonyl chlorides has been developed. Structurally diverse sulfonyl chlorides were synthesized in moderate to excellent yields from S-alkylisothiourea salts, which can be easily prepared from readily accessible alkyl halides or mesylates and inexpensive thiourea, via N-chlorosuccinimide chlorosulfonation. In large-scale syntheses, the byproduct succinimide from ‘waste water’ can be conveniently converted into the starting reagent N-chlorosuccinimide with sodium hypochlorite (bleach) to make the method sustainable.
Keywords: sulfonyl chloride; S-alkylisothioruea; N-chlorosuccinimide; chlorosulfonation; synthesis